2002
DOI: 10.1016/s1472-6483(10)61827-5
|View full text |Cite
|
Sign up to set email alerts
|

Intact follicle culture: what it can tell us aabout the roles of FSH glycoforms during follicle development

Abstract: An important limiting factor in assisted reproduction treatment success rates is oocyte quality. In spite of improved results through several important innovations, the pregnancy rate per collected oocyte remains far too low. In order to improve this situation, it is necessary to learn more about fundamental factors modulating follicular development patterns. FSH is known to be the driving force for follicle development, but it is not yet understood how its multifarious functions are controlled and modulated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 77 publications
4
29
0
2
Order By: Relevance
“…That is to say, high concentrations of FSH and EGF and lower concentrations of GDF-9 and bFGF may be beneficial for the development of primary follicles. Studies on growth factors have demonstrated that FSH and EGF are not essential for primordial follicle activation [24][25][26] but are important for latter follicle development [1,14]. On the other hand, GDF-9 and bFGF can promote the initiation of primordial follicle development and stimulate early preantral follicle growth [5,6,8,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, high concentrations of FSH and EGF and lower concentrations of GDF-9 and bFGF may be beneficial for the development of primary follicles. Studies on growth factors have demonstrated that FSH and EGF are not essential for primordial follicle activation [24][25][26] but are important for latter follicle development [1,14]. On the other hand, GDF-9 and bFGF can promote the initiation of primordial follicle development and stimulate early preantral follicle growth [5,6,8,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the various influences on the growth factors in ovarian follicle development have not been very uniform among different species. Studies have demonstrated the involvement of follicle-stimulating hormone (FSH) [1][2][3], growth and differentiation factor 9 (GDF-9) [4][5][6][7], basic fibroblast growth factor (bFGF) [8][9][10], insulin [11], and epidermal growth factor (EGF) [12][13][14] in early follicular development. Other factors that were incorporated in the present study are based on these references.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that the structure of oligosaccharides present in the FSH molecule induces a differential response in rat GCs in terms of oestradiol production . The pattern of follicular development and oocyte quality in mice are also strongly influenced by rhFSH sialylation (Nayudu et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…FSH isoforms, i.e. protein variants with a different glycosylation profile [3][4][5], regulate distinct biological pathways and have specific effects on granulosa cell function and ovarian follicular maturation [6][7][8][9]. Dynamic changes in FSH isoforms occur during the follicular cycle with short-living forms predominating in the pre-ovulatory phase, whereas long-acting molecules characterize the luteal-follicular transition [10,11].…”
Section: Introductionmentioning
confidence: 99%